Association of Quality of Sleep and Decreased Short Term Memory Function in Medical Students of Pelita Harapan University - Budianto, Stevanie; Siahaan, Yusak M.T (Medicinus, 2020)
Background: Memory is a place where information is stored from the learning process or experience. There are several types of memory , one of them is short term memory. Declining sleep quality is directly proportional to the decrease in short-term memory. Poor sleep quality is often associated with medical student due to exams or vast amount of tasks. Therefore, researcher wants to see whether there is significant correlation between sleep quality and short-term memory function in students.Aim: To assess the association of the quality of sleep towards short term memory function of medical student of Pelita Harapan University.Methods: This study was conducted with a cross-sectional method, with taking sample using the method of a simple random sample. A total of 90 respondents at University of Pelita Harapan were taken. Data collected sorted out according to the inclusion and exclusion criteria. Quality of sleep assessed with PSQI questionnaire while short-term memory assessed by Digit span backward test. Results processed with SPSS version 24 and tested with Chi Square.Results: Data analyzed by Chi square test showed there are 33 students (58.9%) have poor sleep quality and short term memory function. There are also significant association between the quality of sleep and short term memory function (p value = 0.026)Conclusion: There is significant association between the quality of sleep and short term memory function of medical students of Pelita Harapan University.